HUBUNGAN SECURE ATTACHMENT DENGAN KEMANDIRIAN ANAK USIA DINI: The Relationship of Secure attachment Role with Early Children's Independence - I Gusti Ayu Putu Satya Laksmi; Ni Ketut Citrawati (LPPM STIKES Pemkab Jombang, 2022)
Background : As one of the developmental tasks in early childhood, independence needs to be considered and instilled from an early age. The formation of independence in children depends on several factors, one of which is the child's attachment to parents. Objective: to determine the relationship between secure attachment and early childhood independence. Methods : This research is a type of quantitative research with a cross sectional design. The sample consists of 32 people (students and parents) with a total sampling technique. The measuring instrument used to assess secure attachment and independence is a questionnaire. Results : The results showed that the majority of respondents had a moderate level of secure attachment, namely 68.8%, the majority of respondents had a moderate level of independence, namely 71.8%. The results of the bivariant test with the Spearman Ranks test, obtained a p value of 0.005 (p <0.05). Conclusion : The conclusion is that there is a significant relationship (p = 0.005) between Secure Attachment and Early Childhood Independence in Tunas Gama Kindergarten. Based on the results of this study, for further researchers to examine other factors that affect Secure Attachment with Child Independence